Race in Another America : The Significance of Skin Color in Brazil - Telles, Edward Eric, 1956- (Book collections on Project MUSE., 2006)
"This is the most comprehensive and up-to-date book on the increasingly important and controversial subject of race relations in Brazil. Brazilians have commonly compared themselves with North Americans, and have traditionally argued that race relations in Brazil are far more harmonious because the country encourages race mixture rather than formal or informal segregation. More recently, however, scholars have challenged this national myth, seeking to show that race relations are characterized by exclusion, not inclusion, and that fair-skinned Brazilians continue to be privileged and hold a disproportionate share of wealth and power. In this sociological and demographic study, Edward Telles seeks to understand the reality of race in Brazil and how well it squares with these traditional and revisionist views of race relations."--Book cover